Auxiliar de Ingeniería brindando apoyo en actividades de la empresa Grupo Constructor inmobiliario Construcol y Sygemin en Duitama (2022)
This project is based on the development of the internship, carried out in the company Construcol and Sygemin in which support was provided by performing various activities in the administrative part and in the field, such as inspection visits of different works, ordering of building materials, control of entry and exit of equipment and / or materials, inspecting tha t the compliance with the proposed parameters according to the plans and designs, among others specified in the daily logs is properly performed, Allowing me to grow professionally and consolidating the knowledge acquired at the University Antonio Nariño, contributing to the enrichment of my practical knowledge and where it is achieved to place at the disposal of the practice the knowledge acquired in the course of my training studies, where you can learn and gain experience in a professional life on profes engineering projects.